Poststructuralist-Feminist International Relations: A Point of Reconciliation? - Lailatul Fitriyah (Department of International Relations, Universitas Andalas, 2015)
The relationships between peace studies and international relations (IR) has never been easy. The “strategic” nature of inter-state relations in IR and its state-centric focus are some of the big challenges to the humanitarian nature of peace studies. However, the rise of feminism in IR in the 1980s has given us a new promise in opening the field of IR to a greater humanitarian focus which could take even the individual level of analysis into account. IR poststructuralist-feminism - which is understood as an IR feminist perspective which deconstruct the “common assumptions of culture” (Sylvester, 1994) including feminism itself - is particularly progressive in the sense that it does not only provide the room to problematize the basic assumptions of mainstream IR, but also room to even question the premises of the IR feminists themselves, a self-reflective quality shared by contemporary peace studies. One of the latest theoretical developments in poststructuralist-feminist IR is the “adoption” of positive psychology into IR methodology in order to take a deeper look into the mostly forgotten dimension of humans’ capability to flourish even under the most extreme condition (Penttinen, 2013). Again, this new proposal resonates with the current trend in peace studies scholarship in which peacebuilding processes are geared toward fuller ownership by the locals and harnesses their capabilities to survive. This article would like to analyze the potentialities of feminist approaches in IR, particularly those which come from the poststructuralist school of thought, as a fruitful “meeting point” for peace studies and IR. Once we identify the “meeting point,” hopefully it can bring us into a rich inter-disciplinary endeavor in the future as well as a better understanding of the dynamics of peacebuilding practices in the context of international relations.Key Words: international relations, poststructuralist feminist IR, peace studies, positive psychology, reflective practices